Packed media radiative-transfer modeling with Gaussian particles: Application to spectra of icy regolith of Saturnian satellites. (November 2022) - Ito, Gen; Kolokolova, Ludmilla; Petrov, Dmitry; Pitman, Karly M.
Highlights: Packed media are modeled by radiative transfer with static structure factor, RTT-PM. Gaussian particles in packed media scheme effectively model icy regolith spectra. Parameters of the shape of Saturnian moon regolith particles have been found. The model balances physical rigor with practicality and is promising for large data. Abstract: The radiative transfer theory with packed media correction (RTT-PM) is a balanced, physically rigorous, and practical light scattering model that is suitable for modeling reflectance and similar spectra of densely packed particulate media. The static structure factor correction to the classical radiative transfer solution and actualization of fundamental particles of media with spheres or aggregates are key properties of this model that ensure both physical rigor and practical efficiency. We improved upon the assumptions in the RTT-PM method by incorporating irregularly shaped Gaussian particles into its scheme. This incorporation of Gaussian particles is a notable advancement for applications of the RTT-PM method to planetary surfaces that often are layers of irregularly shaped particles. With the Gaussian particle RTT-PM method, we modeled spectra of Saturnian moons Dione, Rhea, and Tethys observed with the Cassini Visual and Infrared Mapping Spectrometer (VIMS), assuming pure water ice composition. For Rhea and Tethys, the Gaussian particle RTT-PM technique modeled VIMS spectra better than models with spherical or aggregate particles, strengthening prior suggestion that particles on Rhea and Tethys are solid, non-spherical particles. Dione's spectra were best modeled not with Gaussian particles but rather with an aggregate of 128 monomers. This makes Dione's icy regolith different from that on Rhea and Tethys. Prior studies have indicated that the cause for the difference might arise from the presence of surface macrostructures or absorbing materials on Dione, but according to our modeling results, increased multiple scattering from small fluffy aggregate particles is an alternative explanation.